Identification and characterization of senescent macrophages in renal allograft rejection: a cross-species MultiOmics study - Xiao, Hanyu; Zhang, Jie; Pang, Qidan; Yu, Chengjun; Pei, Jun; Wang, Huyu; Wen, Sheng; Long, Chunlan; Hua, Yi; Wei, Guanghui (Frontiers in Immunology, 2025)
BackgroundAllograft rejection remains a main hindrance for long-term graft survival. Cellular senescence (CS) contributes to graft injury, but the role of immune cell senescence in rejection remains unclear.MethodsMicroarray data from renal transplant biopsy cohorts and age-matched rat allograft models were integrated to characterize senescence phenotypes. Immune cell infiltration algorithms and histopathology were employed to recognize major senescent alloimmune subpopulation. Then, novel senescent infiltrating macrophages (SnIMs) were identified using cross-species single-cell transcriptomics and validated in rat models. Finally, the clinical values of SnIMs were evaluated in renal transplant datasets.ResultsCS gene sets were enriched in rejecting allografts, correlating with graft loss and pathological injury. Alloimmune responses amplified stress-induced senescence in rat allografts, with p21+ macrophages emerging as the important senescent immune subtype. SnIMs exhibited cell cycle arrest, upregulation of senescence-associated secretory phenotype, and conserved transcriptional signatures driven by NF-κB/Cebpb across species through single-cell analysis. These cells accumulated along pseudotime during rejection and interacted with effector T cells via CXCL chemokines. Clinically, SnIM infiltration predicted T cell–mediated rejection and correlated with Banff lesion grades and poor graft survival.ConclusionsOur findings identify novel stress-induced SnIMs in renal allograft rejection and highlight their pathogenic role in rejection injury, providing a therapeutic target to improve renal transplant outcome.